Education as the space of individual’s personality development - Sokolnicka, Anna (Paedagogia Christiana, 2009)
A man in XXI century is too often being made by society just as a consumer of goods and pop-culture. In educational practice there is usually also more important to have than to be. That is why is so necessary to consider the meaning, which education could have today. The author (of this article) thinks, that it should be the space of individual’s personality development. For make this situation possible we must respect those pedagogical cathegories like: dialogue, empowerment, sociological ambivalence or borderlands. That is the only way for making education more human and more useful for everyone. Lastly we must notice that in such matter, asking question might be more difficult but also more essential than reply to them. 36